Role of Bismuth in Cobalt Spinel Ferrite. (2015) - Anjum, Safia; Sehar, Fatima; Bashir, F.; Awan, M.S.; Mustafa, Zeeshan
Abstract: The current project deals with the synthesis and characterization of bismuth doped cobalt ferrite with general formula of CoBix Fe(2-x) O4 (where x varies from zero to 0.5 with the step size of 0.1). This series have been prepared using powder metallurgy route. The structural, chemical, morphological, elemental, magnetic and optical properties have been investigated using XRD, FTIR, SEM, EDX, VSM and UV Visible spectrometer respectively. Structural measurements show the confirmation of spinel structure. This also shows the decrease in lattice parameters and crystallite sizes, which are due to the replacement of larger cations Fe +3 by smaller cations Bi +3 . Functional groups or characteristic bonds of spinel ferrites have been investigated by FTIR spectrum. SEM micro graphs revealed the spherical shape of the particles, also shows the un-even or non-uniform grain boundaries. An EDX spectrum confirms the elemental composition of the prepared ferrites. UV-Visible spectrometer revealed the increase in band gap with the decrease in grain size. VSM reveals that saturation magnetization decreases with the increase of bismuth oxide content in CoBix Fe(2-x) O4 .